Simple Screening Tests for the Detection of Metallo-β-Lactamase (MBL) Production in Clinical Isolates of Pseudomonas and Acinetobacter (Ibrahim Medical College Journal, 2010)
There are no standard methods for the detection of metallo-β-lactamase (MBL) production in gramnegative organism in routine microbiology practice. The present study was undertaken to evaluatethe screening tests like double disk synergy test (DDST) and disk potentiation test (DPT) usingceftazidime (CAZ) and imipenem (IPM) disks with chelating agents like EDTA, 2-mercaptopropionicacid (2-MPA). A total of 132 Pseudomonas and 76 Acinetobacter isolates were obtained fromBangabandhu Sheikh Mujib Medical University (BSMMU) and Bangladesh Institute of Researchand Rehabilitation for Diabetes, Endocrine and Metabolic Disorders (BIRDEM) hospitals of Dhakacity. A total of 53 and 29 IPM resistant Pseudomonas and Acinetobacter isolates were selected.EDTA-IPM microdilution minimum inhibitory concentration (EDTA-IPM MIC) method detectedMBL in 44 (83%) IPM resistant Pseudomonas and 19 (65.5%) Acinetobacter isolates. DDST withCAZ-0.1M EDTA and CAZ-2-MPA detected MBL in 73.6% and 67.9% of IPM resistant Pseudomonasand 55.2% and 48.3% of Acinetobacter isolates respectively. The detection rate was 67.9% and66.1% in Pseudomonas and 51.7% and 44.8% in Acinetobacter isolates by EDTA-IPM and IPM-2-MPA methods respectively. In comparison to DDST, DPT with CAZ-0.1M EDTA showed highersensitivity (89.7% ) and specificity (100%) for detection of MBL in Pseudomonas and Acinetobacter.The results showed that simple screening tests like DPT with 0.1M EDTA was able to detect MBLproducing Pseudomonas and Acinetobacter from clinical samples with high sensitivity and specificity.Ibrahim Med. Coll. J. 2010; 4(1): 26-30DOI: 10.3329/imcj.v4i1.5932